A Study On Problems And Challenges Faced By Female College Students In Thoothukudi - et. al., S.Vedhavalli, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Our India is a developing country moreover it is one of the largest democracies. Since the day of independence, our country has remarkable development in all fields. And this was all possible because of the increase in education. we can say that women’s education is a major step toward success. Women’s literacy rate is increasing day by day but still due to some reasons the growth is hampering. The main reason for this is a crime against women various crime against women take place every day. Because of which women are not able to roam freely on the roads. Also gender discrimination and male superiority are still common. This is one of the main reasons for the reduced women literacy in the entire country. However, there are many steps that the government is taking to promote women’s education.This paper attempts to ascertain the challenges faced by female students in higher education.